Advances in 3D‐Sensing Technologies and Applications. Issue 6 (1st November 2015) - Bhowmik, Achintya K.; BenHimane, Selim; Kutliroff, Gershom; Rand, Chaim; Ho, Hon Pong
Abstract : 3D sensing enabled by depth‐imaging technologies allows immersive user interfaces and lifelike interactive experiences via real‐time understanding of the 3D environment, people, and objects in real‐world scenes. Advances in this area are being made possible through several key technologies, including sensors, algorithms, and system integration.